The iron-oxidizing proteobacteria - Hedrich, Sabrina; Schlömann, Michael; Johnson, D Barrie (Microbiology (Society for General Microbiology), 2011)
The 'iron bacteria' are a collection of morphologically and phylogenetically heterogeneous prokaryotes. They include some of the first micro-organisms to be observed and described, and continue to be the subject of a considerable body of fundamental and applied microbiological research. While species of iron-oxidizing bacteria can be found in many different phyla, most are affiliated with the Proteobacteria. The latter can be subdivided into four main physiological groups: (i) acidophilic, aerobic iron oxidizers; (ii) neutrophilic, aerobic iron oxidizers; (iii) neutrophilic, anaerobic (nitrate-dependent) iron oxidizers; and (iv) anaerobic photosynthetic iron oxidizers. Some species (mostly acidophiles) can reduce ferric iron as well as oxidize ferrous iron, depending on prevailing environmental conditions. This review describes what is currently known about the phylogenetic and physiological diversity of the iron-oxidizing proteobacteria, their significance in the environment (on the global and micro scales), and their increasing importance in biotechnology.